Dynamic equivalent model of VSC based on singular perturbation. Issue 14 (1st November 2016) - Yuan, Zheng; Du, Zhengchun; Li, Chongtao; An, Ting
Abstract : Scalable and computationally efficient model of voltage source converter (VSC) that accurately captures the dynamics is key to the modelling, analysis and control of VSC–high‐voltage direct current system. In this study, a dynamic equivalent model of VSC including the dynamics of control system is obtained by using singular perturbation method for the first time. The reduced second‐order model with simple form and good generality captures the steady‐state and transient behaviours of original full model with a high degree of accuracy. This equivalent model retains the physical meaning of the variables, accommodates different control modes and significantly reduces the computational burden compared with the original full model. Singular perturbation method itself contains some systematic procedures to be able to improve the accuracy of the dynamic behaviour of the lower‐order model. The ability of the dynamic equivalent model to accurately describe the original dynamics of the system has been verified with numerical simulations in normal operation and on fault case associated with MTDC grids.